Characterization of the complete mitochondrial genome and phylogenetic analysis of the Southern giant petrel (Macronectes giganteus, Procellariiformes: Procellariidae) - Jong-U Kim; Jeong-Hoon Kim (Mitochondrial DNA. Part B. Resources)
The Southern giant petrel (Macronectes giganteus (Gmelin, 1789)) is a large seabird widely distributed in the southern oceans. In the present study, the complete mitochondrial genome of M. giganteus was sequenced and characterized for the first time. The mitogenome sequence was circular and 20,169 bp in length. It contains 13 protein-coding genes (PCGs) including one cis-slicing gene (ND3), 22 transfer RNA (tRNA) genes, and two ribosomal RNA (rRNA) genes. Furthermore, there was an additional copy of two tRNAs and ND6 due to a 2.9kbp duplication. The total nucleotide composition was 30.84% (A), 30.69% (C), 13.05% (G), and 25.42% (T) with an overall GC content of 43.97%. Phylogenetic analysis of all PCGs in the complete mitogenome confirmed the inclusion of M. giganteus within the family Procellariidae. These new mitochondrial genome data will be useful for further studies on the phylogenetics and evolutionary history of the family Procellariidae and genus Macronectes.